2018
DOI: 10.1016/s2214-109x(18)30022-6
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis control interventions targeted to previously treated people in a high-incidence setting: a modelling study

Abstract: Summary Background In high-incidence settings, recurrent disease among previously treated individuals contributes substantially to the burden of incident and prevalent tuberculosis. The extent to which interventions targeted to this high-risk group can improve tuberculosis control has not been established. We aimed to project the population-level effect of control interventions targeted to individuals with a history of previous tuberculosis treatment in a high-incidence setting. Methods We developed a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…6 To our knowledge, our study is the first to estimate the costeffectiveness of interventions targeted to people with a history of previous tuberculosis treatment in a highincidence setting. It extends findings of an earlier modelling study, 12 in which we found that offering tuberculosis case finding and secondary IPT to people previously treated for tuberculosis could greatly accelerate declines in tuberculosis incidence and mor tality in this setting. Both studies support the proposition that in settings with a high incidence of tuberculosis, previously treated people constitute an important group that might be especially attractive for targeted interventions given their high risk of recurrent tuberculosis and their probable role in transmission of M tuberculosis in the population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…6 To our knowledge, our study is the first to estimate the costeffectiveness of interventions targeted to people with a history of previous tuberculosis treatment in a highincidence setting. It extends findings of an earlier modelling study, 12 in which we found that offering tuberculosis case finding and secondary IPT to people previously treated for tuberculosis could greatly accelerate declines in tuberculosis incidence and mor tality in this setting. Both studies support the proposition that in settings with a high incidence of tuberculosis, previously treated people constitute an important group that might be especially attractive for targeted interventions given their high risk of recurrent tuberculosis and their probable role in transmission of M tuberculosis in the population.…”
Section: Discussionsupporting
confidence: 87%
“…The transmissiondynamic model is an extension of a model that we previously used to explore the impact of targeted active case finding and secondary IPT after tuberculosis treatment completion in the same study setting. 12 The tuberculosis component of the model follows the conventions of earlier models [13][14][15][16] with additional structure to distinguish between individuals who have never been treated for tuberculosis (treatment naive) and those who have previously been treated for tuberculosis (treatment experienced; figure 1). Model transitions are fully described in the appendix (pp 2-3).…”
Section: Modelling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This was particularly true for people with recurrent TB, with almost 100% notified by PCF. It is well known that cases notified by PCF will suffer a longer diagnostic delay than those notified by active case finding (ACF) [16]. This could partly explain why people with recurrent TB have longer delays.…”
Section: Discussionmentioning
confidence: 99%
“…This is a general phenomenon in infectious diseases, although there may be exceptional circumstances where the sign of the effect may be reversed as detailed below. In any case, it is a systematic error (bias) not to be confused with uncertainty in parameter estimates 19,20 .…”
Section: Resultsmentioning
confidence: 99%